Transport on a Human Scale - World Bank (World Bank, 2012)
An efficient and affordable access to jobs, education and services is considered a fundamental element for development. However, the mobility conditions in the cities have deteriorated because of the increasing motorization and urbanization. The number of new cars that enter the cities every year outpaces the construction of new roads, aggravating the existing congestion issues. Therefore, the urban models that revolve around highways and private vehicles are frequently questioned. These models ignore the individual and humane factors as the primary structure of the city. Nowadays, the public transport systems and the non-motorized modes are considered to be the pillars of mobility, connectivity and accessibility. The National Urban Transport Program (NUTP) in Colombia is focused in developing public transport systems as the central element of urban mobility. A mass transport that is fast, comfortable, clean and safe will increase urban productivity and improve the quality of life. Based on this hypothesis, and through the NUTP, the Central Government provides financial and technical support to cities of 600,000 or more inhabitants in order to implement brand new mass transport systems. The program is supported on a solid base formed by the Central Government, the Municipalities and the private sector. Transport on a human scale shows a different dimension of the impacts of a program such as the NUTP. This impact is illustrated from the perspective of testimonials. The book shows, on each of the 'stations', different elements that illustrate the creation of more humane and inclusive cities. Moreover, it portrays the experiences and thoughts of leaders, experts and users through a wide array of graphics and texts.